Follow-up of pregnancy and delivery in a patient with polymyositis: Case report - Kavak, Salih Burçin; Karakaya, Fethi; Güngör, Sami; Baykuş, Yakup (My University, 2012)
Polymyositis is a subacute inflammatory myopathy, which is rarely been in pregnancy. Good fetal prognosis is mostly depend on remission of the disease. Increase of blood levels of muscle enzymes and specific signs of polymyositis in electromyogram are seen. We herein report a 28 years old woman with polymyositis whose pregnancy was followed from 8 weeks of pregnancy. Drugs used for polymyositis were regulated and pregnancy was terminated by cesarean section by using regional anesthesia. Copyright © 2012 by Türkiye Klinikleri.
Bir polimiyozit olgusunda gebelik takibi ve do?um
Keywords: Polymyositis; Pregnancy